2016
DOI: 10.1590/1980-5373-mr-2015-0593
|View full text |Cite
|
Sign up to set email alerts
|

Development of nano-oxide dispersed 304L steels by mechanical milling and conventional sintering

Abstract: In the present work an attempt has been made to synthesize 304L stainless steels alloy powders with nominal compositions 70.00Fe-19.00Cr-11.00Ni (alloy A), 69.00Fe-19.00Cr-11.00Ni-1.0 Y 2 O 3 (alloy B), and 69.00Fe-19.00Cr-11.00Ni-1.0 TiO 2 (alloy C), (all in wt.%) by mechanical milling and conventional sintering at 1150°C for 1.0 hour in argon atmosphere. Extensive characterization has been done by SEM, TEM, X-ray diffraction analysis, EDS and particle size analysis at different stages of milling. The minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Karak et Al. developed 304 L austenitic stainless steel dispersed with 1 wt-% Y 2 O 3 [41]. SEM-EDS studies revealed the formation of ferrite phase which is due to the presence of high chromium content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karak et Al. developed 304 L austenitic stainless steel dispersed with 1 wt-% Y 2 O 3 [41]. SEM-EDS studies revealed the formation of ferrite phase which is due to the presence of high chromium content.…”
Section: Resultsmentioning
confidence: 99%
“…Few researchers studied the development of austenitic stainless steel, as dispersed with Y 2 O 3 . Karak et al developed 304 L austenitic stainless steel dispersed with 1 wt-% Y 2 O 3 [41]. SEM-EDS studies revealed the formation of ferrite phase which is due to the presence of high chromium content.…”
Section: Sem-eds Studiesmentioning
confidence: 99%
“…Kumar et al fabricated Y2O3/TiO2 reinforced 304L stainless steel nanocomposites using mechanical alloying (MA). They reported that the hardness and wear resistance grew with the addition of nanoparticle reinforcement in a 304L steel matrix [7]. Zou et al investigated the laser powder bed fusion (LPBF) of SiC-reinforced 316L stainless steel metallic matrix composites (MMCs) to improve the ultimate tensile strength and wear resistance.…”
Section: Introductionmentioning
confidence: 99%